Definition and concepts in aestetics - Sułkowska, Mariola (Folia Philosophica, 2000)
The present article relates the discussion about the definition of aesthetics and the concepts used in it. The author presents the views of, mainly Anglo-Saxon, thinkers, such as Clive Bell, Morris Weitz, Timothy Binkley, and Robert J. Matthews. The problems and controversies connected with the subject of the article are considered in the context of an aesthetic argumentation.